A mixed methods study to assess the effectiveness of food-based interventions to prevent stunting among children under-five years in Districts Thatta and Sujawal, Sindh Province, Pakistan: study protocol. (December 2017) - Kureishy, Sumra; Khan, Gul; Arrif, Shabina; Ashraf, Khizar; Cespedes, Angela; Habib, Muhammad; Hussain, Imtiaz; Ullah, Asmat; Turab, Ali; Ahmed, Imran; Zaidi, Shehla; Soofi, Sajid
Abstract Background Maternal and child malnutrition is widely prevalent in low and middle income countries. In Pakistan, widespread food insecurity and malnutrition are the main contributors to poor health, low survival rates and the loss of human capital development. The nutritional status trends among children exhibit a continuous deteriorating with rates of malnutrition exceeding the WHO critical threshold. With the high prevalence of maternal and child malnutrition, it is important to identify effective preventative approaches, especially for reducing stunting in children under-five years of age. The primary aim of this study is to assess the effectiveness of food-based interventions to prevent stunting in children under-five years. Methods A mixed methods study design will be conducted to evaluate the effectiveness of food-based interventions to prevent stunting among children under-five years in districts Thatta and Sujawal, Sindh Province, Pakistan. The study will include cross sectional surveys, a community-based cluster randomized controlled trial and a process evaluation. The study participants will be pregnant women, lactating mothers and children under-five years. The cross-sectional surveys will be conducted with 7360 study participants at baseline and endline. For the randomized control trial, 5000 participants will be recruited and followed monthly for compliance of food-based supplements, dietary diversity, pregnancy outcomes, and maternal and child morbidity and mortality. Anthropometric measurements and hemoglobin levels will be measured at baseline, quarterly and at endline. The interventions will consist of locally produced lipid-based nutrient supplement (Wawamum) for children 6–23 months, micronutrient powders for children 24–59 months, and wheat soya blends for pregnant and lactating mothers. Government lady health workers will deliver interventions to participants. The effectiveness of the project will be measured in terms of the impact of the proposed interventions on stunting, nutritional status, micronutrient deficiencies, and other key indicators of the participants. The process evaluation will assess the acceptability, feasibility and potential barriers of project implementation through focus group discussions, key informant interviews and household surveys. Data analysis will be conducted using STATA version 12. Discussion There is considerable evidence on the effectiveness of food-based interventions in managing stunting in developing countries. However, these studies do not account for the local environmental factors and widespread nutrient deficiencies in Pakistan. These studies are often conducted in controlled environments, where the results cannot be generalized to programs operating under field conditions. The findings of this study will provide sufficient evidence to develop policies and programs aimed to prevent stunting in children 6–59 months and to improve maternal and child health and growth outcomes in poor resource settings. Trial registration NCT02422953 . Registered on April 15, 2015.